Pemberdayaan Kelompok Petani Aren Dusun Batu Delapan Desa Rantau Kecamatan Rantau Pauh Kabupaten Aceh Tamiang - M Raka Siwi; Firdaus Mirza Nusuary; Ibnu Phonna Nurdin (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The community empowerment program for sugar palm farmers in Dusun Batu Delapan through the CSR program Meghgek Betuah of PT Pertamina aims to enhance farmers' production capacity. However, challenges related to limited land and raw materials have hindered the sustainability of this program. This study aims to examine the implementation of the Meghgek Betuah program in Batu Delapan. The research method employed is a qualitative approach with a case study design, utilizing data collection techniques such as observation, interviews, and documentation.The findings indicate that the program has not been optimal in increasing sugar palm production. Among the four aspects of community empowerment proposed by Robert Chambers (people-centered, participation, empowerment, and sustainability), only the sustainability aspect has not been fully achieved. The limited availability of raw materials and land has prevented farmers from significantly increasing production. The other three aspects—people-centered, participation, and empowerment—have been met, as evidenced by the implementation of training, active participation of farmers, and the application of training outcomes in the farmers' daily activities. Overall, while the program has succeeded in certain aspects, sustainability remains a key challenge in improving sugar palm production in Batu Delapan.